The Emerging Roles and Therapeutic Potential of Soluble TREM2 in Alzheimer’s Disease - Zhong, Li; Chen, Xiao-Fen (Frontiers in Aging Neuroscience, 2019)
Alzheimer’s disease (AD) is the most common form of dementia characterized by the deposition of extracellular amyloid-β (Aβ)-containing plaques, the formation of intraneuronal neurofibrillary tangles as well as neuroinflammatory changes. As the key player in the brain innate immune system, microglia has now taken a center stage in AD research. A large number of AD risk loci identified by genome-wide association studies are located in or near the genes highly expressed in microglia. Among them, the triggering receptor expressed on myeloid cells 2 (TREM2) has drawn much attention. A rare variant in TREM2 increases AD risk with an odds ratio comparable to the strongest genetic risk factor apolipoprotein ε4 allele. In the past 6 years, extensive studies have dissected the mechanisms by which TREM2 and its variants modulate microglial functions impacting amyloid and tau pathologies in both animal models and human studies. In addition to the full-length TREM2, research on the soluble form of TREM2 (sTREM2) has facilitated the translation of preclinical findings on TREM2. In this review, we summarize our current understanding of the biology and pathobiology of sTREM2 including its origin, its emergence as a disease biomarker, and its potential neuroprotective functions. These aspects are important for understanding the involvement of sTREM2 in AD pathogenesis and may provide novel insights into applying sTREM2 for AD diagnosis and therapy.